THE EFFECT OF BEACH ENVIRONMENT AND SEA WATER ON NICKEL CORROSION RATE AS A COLLIMATOR MATERIAL FOR THE APPLICATION OF BORON NEUTRON CAPTURE THERAPY - Hardi Hidayat; Budi Setyahandana; Yohannes Sardjono; Yulwido Adi (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2019)
The purpose of this study is to determine the value of corrosion rate influenced by coastal environment and seawater to nickel as a collimator base material for the application of boron neutron capture therapy (BNCT). In this research, the authors used 99.9% pure nickel as the reference material. Corrosion testing was carried out to determine the rate of corrosion of nickel as a base material for BNCT. After the specimens were formed, the test specimens were then corroded for 12 weeks, with various conditions such as indoor, outdoor environment, static seawater, and moving seawater. The results of this study indicated that in corrosion testing with indoor condition, the corrosion rate values are 0.61-1.00 mpy. For outdoor condition, the corrosion rate is 0.89-1.34 mpy. Meanwhile, at static seawater conditions, the corrosion rate is 0.97-1.24 mpy. Lastly, for moving seawater condition, the corrosion rate is 1.64-1.91 mpy. The results showed that corrosion resistance was relatively the same for all nickel exposed to corrosion in the coastal environment. Therefore, in regards to corrosion resistance, using nickel as a collimator base material for BNCT applications is considered as safe.Keywords: BNCT, Nickel, Corrosion, Coastal Environtment, Sea Water